Assessment of natural radioactivity and associated radiological risks from soils of Hakim Gara quarry sites in Ethiopia - Regassa, T.N.; Raba, G.A.; Chekol, B.M.; Kpeglo, D.O. (Heliyon, 2023)
One of the ways of minimizing radiation risks to workers and the public is assessing potential sites that are suspected of producing radiation. Among such locations, quarry sites stand out because areas of granite and other rocks, especially those of uranium family potentially have high con centrations of radiation. This study was aimed to assess one such quarry sites (Hakim Gara site), located near Harar town, Harari region-Ethiopia. To assess the radiological impact of natural radioactivity of quarry activities in the study area, activity concentrations of natural radionu clides 238U, 232Th, 226Ra and 40K in the soil samples were investigated by collecting twenty composite soil samples from different sites of the area. Measurements were carried out using high purity germanium (HPGe) Gamma Spectrometry detecting system for acquisition of data and making analysis using Genie 2000 software. From the result, mean Activity concentration of 238U, 232Th and 40K obtained were 51.9 ± 15 Bq/kg, 68.32 ± 9.75 Bq/kg and 220.0 ± 2.0 Bq/kg, respectively. Average Activity concentration of the 226Ra was 32.71 ± 2.02 Bq/kg. These values were used to calculate and estimate the radiological risks due to environmental radiation expo sure contributed from the quarrying activities. The average external and internal hazard indices were 0.45 ± 0.09 mSv/y and 0.49 ± 0.23 mSv/y both of which were below the permissible limit of unity. The results obtained for 238U and 232Th were higher and significant from the world average which need further regulatory monitoring. The level of 40K was below the world average. Hence, this research provided a foundation for future studies on subsequent investigations and to aid realistic regulatory and policy decisions.
Research Article
Keywords: Radioactivity concentration; 238U; 232Th; 40K; Hazard indices; Gamma spectrometry